Missiological responses to the wounded youth : a case study of the campus ministry of Scripture Union in the Kumasi metropolis of Ghana - Awuah-Gyawu, Daniel (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.